Investigation of the child with an acute metabolic disorder. Issue 3 (22nd January 2011) - Cook, P; Walker, V
Abstract : Inherited biochemical defects may present with acute life-threatening illness with a high mortality and morbidity. Some are treatable and have a good outcome with early appropriate intervention. However, because of their rarity, diagnosis is often delayed; they are not considered or investigated appropriately. This is especially likely in those presenting in previously healthy adults. The collection of acute samples is crucial. There are numerous disorders, and front-line tests must cast a wide net. A small core of emergency tests generally indicates which metabolic pathway is defective and provides a working diagnosis and basis for treatment. Later confirmation and identification of the precise defect are essential for long-term management and for genetic counselling and prenatal diagnosis of future pregnancies. An escalating number of specialist tests and mutation analyses are undertaken by metabolic laboratories worldwide, but they are not widely available, are expensive, and must be requested selectively. Guidelines are presented here for the front-line investigation of acutely ill children with hypoglycaemia, metabolic acidosis, encephalopathy and intractable seizures, and for a dying child with a suspected, undiagnosed, inherited metabolic defect. With modification, these are also applicable to adults with a metabolic defect. In order to guide further investigation, selected disorders are described briefly along with their diagnostic work-up. Information about sample collection and processing is provided.